Post-COVID Opsoclonus Myoclonus Syndrome: A Case Report From Pakistan - Ishaq, Hira; Durrani, Talha; Umar, Zainab; Khan, Nemat; McCombe, Pamela; Ul Haq, Mian Ayaz (Frontiers in Neurology, 2021)
Background: Coronavirus disease-2019 (COVID-19), caused by the severe acute respiratory distress syndrome–coronavirus-2 (SARS-CoV-2), is primarily a respiratory infection but has been recently associated with a variety of neurological symptoms. We present herewith a COVID-19 case manifesting as opsoclonus-myoclonus syndrome (OMS), a rare neurological disorder. Case Presentation: A 63-year-old male diagnosed with COVID-19 infection developed behavioral changes, confusion, and insomnia followed by reduced mobility and abnormal eye movements within 48 h of recovery from respiratory symptoms associated with COVID-19. On examination, he had rapid, chaotic, involuntary saccadic, multidirectional eye movements (opsoclonus), and limb myoclonus together with truncal ataxia. CSF analysis, MRI of the brain, and screening for anti-neuronal and encephalitis related antibodies were negative. Extensive testing revealed no underlying malignancy. The patient was successfully treated with intravenous immunoglobulin (IVIG) with complete resolution of symptoms within 4 weeks of treatment. Conclusion: COVID-19 infection can be associated with the manifestation of opsoclonus myoclonus syndrome, a rare neurological disorder that can be treated with IVIG if not responsive to corticosteroids.